O PROGRAMA DE DESENVOLVIMENTO DE FORNECEDORES DO ESTADO DO MARANHÃO (PDF-MA) EM QUESTÃO: Avaliando os processos de formulação e implementação de 1999 a 2007 - Hossoé, Heric Santos (2013)
This dissertation focuses the formulation and implementation of the Supplier Development Program of the State of Maranhão. It is worth noting that this program emerges the need of big business and the state to offer a response to local entrepreneurs and society in order to integrate them into the supply chains of large companies. However, to this end, we draw the path from the change in the economy, taking as starting point the private sector, which adopts the restructuring process as this new flagship model, the unbundling of the leading chains of large companies, mainly through outsourcing, thus generating a strategy of regional specialization. Given these changes, turns to examine the paradigm in relation to the State, which is undergoing deep changes, culminating with the so-called Minimum or Neoliberal State. It should be emphasized that the evaluation of the MA-developed PDF is dynamic and want to go from the general international economic relations, through the reflections of these relations in Brazil, reaching the more specific, the program exposed. Finally, the study of the PDF-MA aims to detail the dynamics of the program, building a framework of indicators and developing the theme of Sustainable Development. To undertake such research were two moments evaluative, first we make a political assessment of the policy, so you can figure out the nuances and how its implementation was determined politically, understanding how the program came into the government's agenda and what subjects interest and rationalities involved. In the second, reveals the dynamics of implementation of this policy through an evaluation process, ensuring that the means used are appropriate to the desired ends and if it was able to change the situation that gave rise to the problem program. Along the way, we used a qualitative and quantitative approach, having as research techniques, literature and documentary mode. Thus, we intend to unveil a new vision for the PDF-MA.